Nurses' stressors and their quality of life: A study on nurses caring for older patients - Huda A. Anshasi; Mirna Fawaz; Sura Alhalalmeh; Wafa Qasem Ahmad; Ahmad Tassi (Wiley, 2020)
Abstract Aim To determine the sources of occupational stress and the level of quality of life among nurses caring for older people in Lebanon and examine the underlying factors to predict nurses' quality of life. Design A descriptive correlational design. Methods Data were collected from 119 nurses using Nursing Stress Scale and WHO‐Quality of Life Brief. Results Nurses reported the highest frequency of stressful events related to their workload (mean = 16.42, SD 1.03), followed by "death and dying" (mean = 14.61, SD 1.02). Nurses reported the highest level of quality of life domains was physical health (mean = 15.74, SD = 2.63), while the lowest level was environmental domain (mean = 11.15, SD = 1.86). After controlling for demographic and work‐related variables, occupational stress explained a large variance in the physical (R2 change = .43), psychological (R2 change = .44) and social relationship (R2 change = .35) domains of quality of life.